Collection and storage of Expressed Breast Milk: Policy Analysis paper - Al-Shatnawi, Fida`a Eid; Abu-shaikha, Hayat Sulieman; Alosoufe, Liath Mahmmoud (Journal of Neonatal Surgery, 2025)
Breast milk is the gold standard of nutrition even for healthy and unhealthy newborns. Infants who are hospitalized in NICUs are unable to be fed by their mothers. Thus, expressed breast milk (EBM) from their own mothers should be administered by the nurse in another way. Proper expression, collection, storage and collection of EBM should be considered because breast milk is a body fluid and have the probability for contamination, improper storage and administration. The purpose of this paper is to analyze the issue of breast milk collection and storage for hospitalized infants in the NICUs in Jordanian hospitals. Furthermore, the paper described the appropriate strategies to overcome improper collection, storage and administration of the EBM IN Jordanian hospitals. Eight step guides was used to analyze the issue. Rodriquez-Garcia (2002) five evaluation criteria were also used. After weighing the policy options for their relevancy, progression, impact, effectiveness and efficiency, the bar-coded system was the most appropriate option in order to overcome the improper collection, storage and administration of EBM in hospitalized infants. Policy makers, hospital administrators should consider this system in Jordanian hospital to assure optimal safety for their hospitalized infants.